Risk factors of miscarriage among pregnant women attending Omdurman maternity hospital - Mahmoud, Remaz B.; Saeed, Sara A.; Mustafa, Rana N. (International Journal Of Community Medicine And Public Health, 2023)
Background: Around 56 million miscarriages are performed each year in the world, with about 45% are done unsafely. Miscarriage poses great risks and complications that contribute to long-term physical and psychological problems. Good knowledge and practice related to pregnancy follow-up and avoiding the causes of miscarriage will reduce its risks significantly. Aim of current study was to determine and identify the rate and risk factors of miscarriage and the common causes of miscarriage among women in Omdurman Maternity Hospital, Sudan. In addition, to evaluate the level of awareness of the risks and complications of miscarriage among women attending the maternity hospital, Sudan. Methods: A quantitative, cross sectional study using questionnaires (N=100) was used in this study to determine the risk factors of miscarriage in women attending the maternity hospital in Omdurman, Sudan Results: The study revealed that miscarriages were not very frequent, and there was no significant family history of miscarriages. However, those who had a miscarriage were in the first trimester of pregnancy. One of the main causes of miscarriage is the presence of severe stress from work, illness and food poisoning. Conclusions: The findings of this study suggest different interventions to reduce the risks of miscarriages such as educating mothers about antenatal care and to take precautions during the first trimester to avoid miscarriages and educating families about the risks of being in consanguineous relationships. In addition, raising awareness about contraceptive methods to reduce the rates of induced miscarriages.